(untitled) (Revista Educação, Artes e Inclusão, 2025)
The aim is to take a look at environments that, beyond the school, are also places of education, to enter “other” territories that are not merely traditional intramural school spaces. In this sense, concepts such as cultural pedagogy and critical museology intersect and intertwine, bearing witness to experiences and practices that have an increasing impact on people’s lives, particularly those who have the opportunity to inhabit and live these unique experiences that help us understand and interpret the complex world in which we live and build. Museum spaces, cultural institutions, as well as a huge variety of other public and private places, have therefore been reconfigured in many parts of the world to exhibit not only objects, but also to generate diverse, inclusive and critical narratives that question established knowledge that was thought to be immovable, sometimes dismantling prejudices that were thought to be unquestionable and that affect people’s lives, contributing to new educational paradigms. A meaningful and transformative art education can therefore be produced in these in-between places and intersections, in the countless material or immaterial languages it carries, valuing and making visible multiple histories and perspectives, contributing to the equity and social justice of the world we dare to dream of.